Tantangan dan Peluang di Era Digital Bagi Advokasi Hukum Keluarga Islam - Zahra, Amelda Az; Hanifah, Ikhmatul; Enjelika, Ledy; Fadila, R.A Laras; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Digital transformation has had a significant impact on the pattern of delivery and acceptance of Islamic legal teachings, especially in the field of family law. As one of the important instruments in maintaining social order and protecting family rights, Islamic family law is faced with complex challenges as well as strategic opportunities in the digital era. This study aims to analyze the dynamics of Islamic family law advocacy in the context of advances in information technology, using a qualitative approach based on library studies of relevant literature. The results of the study show that the digital era expands the reach of legal advocacy through various digital platforms such as social media, podcasts, Islamic applications, and online discussion forums. However, the ease of access to information is also accompanied by serious challenges in the form of dissemination of non-authoritative religious content, narrowing of legal substance, and shifting of religious authority from ulama to non-competent digital figures. This reality demands the formulation of a responsive, adaptive, and maqāṣid al-syarī‘ah-based advocacy strategy in order to maintain the authenticity, relevance, and justice of Islamic family law. Advocacy strategies in the digital era need to integrate aspects of legal education, digital literacy, and a collaborative approach between formal institutions, religious figures, academics, and digital communities. The use of technology must be accompanied by strengthening the capacity of ulama and da'i in managing legal communication in a contextual, interesting manner, and still based on sharia principles. Within this framework, advocacy of Islamic family law in the digital era is not only an instrument for disseminating legal norms, but also a transformative medium in building religious awareness and protecting family rights in a more comprehensive and equitable manner.